COMPANY CHARACTERISTICS AND THE TENDENCY OF FRAUDULENT FINANCIAL REPORTING - Kevin Mulyono Teguh; Ari Budi Kristanto (Jurnal Akuntansi Bisnis, 2020)
ABSTRACT : Business environment dynamics may influence the companies performance. In those changing situations, the management is expected to satisfy the expectation of its shareholders, even in the worst position. This requires the management to accomplish various decisions, including those related to financial reporting. The management may tend to convey information about their achievement for the investor’s expectation through accounting numbers. Financial reporting is important as one of the tools that investors use to see deeper to the company. There are several legal ways to make up the report such as accounting method selection. On the other hand, there are also some illegal ways, such as fraud, and manipulation. This research is aimed to find the relation between company characteristics towards the tendency of fraudulent financial reporting. The research data are taken from the Indonesian Stock Exchange and Compustat from 2014 until 2018. The research uses a logistic regression model for data analysis. The result shows that company size, age, and management integrity have negative relation towards the tendency of fraudulent financial reporting. Contrary to the hypothesis, this research found that audit quality has a positive relation to the tendency of fraudulent financial reporting. This research can contribute to society as additional consideration for the investor. Keywords: Company characteristics, fraudulent financial report. ABSTRAK : Dinamika lingkungan bisnis dapat mempengaruhi kinerja perusahaan. Dalam situasi yang berubah tersebut, manajemen diharapkan dapat memenuhi harapan pemegang sahamnya, bahkan pada posisi yang paling buruk sekalipun. Hal ini menuntut manajemen untuk mengambil berbagai keputusan, termasuk yang terkait dengan pelaporan keuangan. Manajemen mungkin cenderung menyampaikan informasi tentang pencapaiannya untuk harapan investor melalui laporan keuangan. Pelaporan keuangan penting sebagai salah satu alat yang digunakan investor untuk melihat lebih dalam perusahaan. Ada beberapa cara legal untuk membuat laporan seperti pemilihan metode akuntansi. Di sisi lain, juga terdapat beberapa cara ilegal, seperti penipuan, dan manipulasi laporan keuangan. Penelitian ini bertujuan untuk mengetahui hubungan antara karakteristik perusahaan dengan kecenderungan pelaporan keuangan yang mengandung kecurangan. Data penelitian diambil dari Bursa Efek Indonesia dan Compustat dari tahun 2014 sampai dengan 2018. Analisis datanya menggunakan model regresi logistik. Hasil penelitian menunjukkan bahwa ukuran perusahaan, umur, dan integritas manajemen berhubungan negatif dengan kecenderungan kecurangan pelaporan keuangan. Bertentangan dengan hipotesis, penelitian ini menemukan bahwa kualitas audit berhubungan positif dengan kecenderungan kecurangan pelaporan keuangan. Penelitian ini dapat memberikan kontribusi kepada masyarakat sebagai pertimbangan tambahan bagi investor.Kata kunci: karakteristik perusahaan, laporan keuangan yang mengandung kecurangan.